Manure management and nutrient cycling in smallholder crop-livestock systems in Nyando, Kenya - Casu, Flavia A. M. (2018)
An essential aspect for smallholder crop-livestock farmers in sub-Saharan Africa is productive soils in order to maintain animal and crop productivity. Often, these systems are heavily dependent on local resources for their input and as a result, manure forms an important by-product to serve as fertiliser for their land. As part of the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS), research on manure management in smallholder farmers in Nyando, western Kenya was done. The aim of this research was to assess manure management practices and current nutrient losses that occur through the manure management cycle. Based on these results, novel management activities were described that could improve current manure management and reduce nutrient losses. A questionnaire was used to acquire data on farm characteristics, manure management and farmers’ perceptions of 20 farms in the Nyando district. Fresh and stored manure samples were taken on-farm and analysed on nutrient content. Based on these results, nutrient losses between fresh and stored manure were calculated. The FARMSIM simulation model was used to calculate herd dynamics and production, especially production of manure. Results showed that between fresh and stored manure, dry matter loss was on average 75% and carbon, nitrogen and phosphorus showed an average loss of 80, 74 and 45%, respectively. On average, 82 kg N ha-1 year-1 was produced, whereas 42 kg N ha-1 year-1 was collected and only 17 kg N ha-1 year-1 was applied on farm. The results indicated that between manure excretion, collection and application large losses occur. Particularly manure collection and method of storage (i.e. manure stored on a heap or in a put, and uncovered or covered with a shed or tree) play an important role. Furthermore, current manure management practices do not provide the farm with sufficient amounts of nutrients needed for a stable crop production. Improvement of manure management practices could reduce nutrient losses and increase overall manure quality. Novel practices include more frequent collection of manure, decreasing the period of storage, covering the manure with a plastic sheet and altering the storage unit in order to reduce nutrient losses through leaching and evaporation.